Central European History and the European Union The Meaning of Europe - Kirschbaum, S.; Kirschbaum, S. (Studies in Central and Eastern Europe, 2007)
This is a volume of scholarly essays that considers the meaning of Europe by examining aspects of Central European history as well as issues dealing with the EU's enlargement into Central Europe. These factors contribute to ideas of a definition of Europe that reflects the values and aspirations of all its citizens.